KAJIAN PROSES EKSTRAKSI SECARA MEKANIS UMBI PORANG TERHADAP FISIKOKIMIA TEPUNG GLUKOMANAN STUDY OF THE MECHANICAL EXTRACTION PROCESS OF PORANG TUBER ON THE PHYSICOCHEMISTRY OF GLUCOMANNAN FLOUR - Bastari, Muhammad Afif; -, Murhadi; -, Subeki; Utomo, Tanto (Jurnal Agroindustri Berkelanjutan, 2024)
Indonesia is of the fourth largest coffee producing countries in the world and is grown in several types of coffee, one of which is robusta coffee. Robusta coffee processing in Indonesia, especially Lampung Province, only uses general processing, which makes the coffee have less value. One way to increase the value of Lampung robusta coffee is by using a fermentation processing method or wine process which is influenced by the conditions and length of the fermentation process. This research aims to determine the effect of conditions, fermentation time, and the interaction between conditions and fermentation time on the coffee wine produced. This research was conducted using a Complete Randomized Block Design (RAKL) with two factorials and three replications. This research used 3 formulations, namely intact skin in dry conditions, intact skin in wet conditions, and peeled skin in dry conditions. The similarity of variances was tested using the Bartlett test, the data was processed using variance analysis to obtain an error variance estimate and continued with the BNT test at the 5% level. This research produced the best coffee wine with  treatment intact skin, dry condition for 30 days of fermentation with an aroma score of 8.00 (fine), a taste score of 8.11 (fine), an aftertaste of 7.77 (very good), an acidity of 8.33 (fine), mouthfell 7.77 (very good), balance 7.89 (very good), Uniform Cups 7.00 (very good), clean cups 7.11 (very good), and overall 8.47 ( fine). Further testing of the best treatment resulted in caffeine levels of 0.27% w/w and chlorogenic acid levels of 0.45% w/w.